Amelioration of cold-induced sweetening in potato by RNAi mediated silencing of StUGPase encoding UDP-glucose pyrophosphorylase - Jaiswal, Sandeep; Paul, Krishnayan; Raman, K. Venkat; Tyagi, Saurabh; Saakre, Manjesh; Tilgam, Jyotsana; Bhattacharjee, Sougata; Vijayan, Joshitha; Mondal, Kalyan Kumar; Sreevathsa, Rohini; Pattanayak, Debasis (Frontiers in Plant Science, 2023)
Cold-induced sweetening (CIS) is an unwanted physiological phenomenon in which reducing sugars (RS) get accumulated in potato (Solanum tuberosum) upon cold storage. High RS content makes potato commercially unsuitable for processing due to the unacceptable brown color in processed products like chips, fries, etc., and the production of a potential carcinogen, acrylamide. UDP-glucose pyrophosphorylase (UGPase) catalyzes the synthesis of UDP-glucose towards the synthesis of sucrose and is also involved in the regulation of CIS in potato. The objective of the present work was RNAi-mediated downregulation of the StUGPase expression level in potato for the development of CIS tolerant potato. Hairpin RNA (hpRNA) gene construct was developed by placing UGPase cDNA fragment in sense and antisense orientation intervened by GBSS intron. Internodal stem explants (cv. Kufri Chipsona-4) were transformed with hpRNA gene construct, and 22 transgenic lines were obtained by PCR screening of putative transformants. Four transgenic lines showed the highest level of RS content reduction following 30 days of cold storage, with reductions in sucrose and RS (glucose & fructose) levels of up to 46% and 57.5%, respectively. Cold stored transgenic potato of these four lines produced acceptable chip colour upon processing. The selected transgenic lines carried two to five copies of the transgene. Northern hybridization revealed an accumulation of siRNA with a concomitant decrease in the StUGPase transcript level in these selected transgenic lines. The present work demonstrates the efficacy of StUGPase silencing in controlling CIS in potato, and the strategy can be employed for the development of CIS tolerant potato varieties.